INTEGRASI SISTEM INFORMASI GEOGRAFI SISTEM PENDUGAAN KESESUAIAN LAHAN UNTUK EVALUASI KESESUAIAN LAHAN TEBU DAN ARAHAN PENGEMBANGAN PERTANIAN DI KABUPATEN GARUT, JAWA BARAT - Elsa Almalia; S Soemarno; Yiyi Sulaeman (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
To establish suitable lands for sugar cane plantation,Â evaluation and suitability of existing land can be made using integration between Geographic Information System (GIS) and Land Suitability Assessment System (SPKL). This study was aimed to obtain the level of land suitability class in Garut regency, and arrange the direction of sugar cane plant development in Garut regency, West Java. The research activity was conducted in Geospatial Information and System Analysis Laboratory at Agricultural Land Resources Center Bogor and Garut Regency. All activities were carried out from April to August 2017. The research stages started from the preparation stage, data processing, field verification, determination of the land management and sugar cane cultivation development. Observation points were determined using purposive sample method based on the difference of limiting factors and accessibility. Results of SPKL program running and data merging on ArcGIS software showed that on sugar cane field in Garut Regency there are three results of land suitability evaluation according to moderately suitable (S2) marginally suitable (S3) and not suitable (N). The results of land suitability evaluation on sugar cane showed that the main limiting factor of growth were five types, i.e. drainage class (rc1), baseÂ saturation (nr2), slope (eh1), average temperature (tc1), and soil depth (rc4). A total number of moderately suitable (S2) land for sugar cane in Garut is 131.558 ha, 514.633 ha for marginally suitable (S3) and 318.387 ha for not suitable (N).